Green entrepreneurship: promoting sustainable growth in Malaysia - Amirrudin, Faizatul Akmam; Mohd Shariff, Balqis (Universiti Teknologi MARA, Terengganu, 2022)
Green entrepreneurship is the activity of consciously addressing environmental and social problems and needs and coming up with brilliant, innovative entrepreneurial ideas that will bring a solution to them (iED, 2020). In other words, green entrepreneurship refers to businesses and companies developing products or services that are usable everywhere and have the potential to protect the ecosystem. They must simultaneously ensure that the solutions will not have a detrimental financial impact on the company. While green entrepreneurs are individuals or groups who identify environmental problems and seek to develop innovative solutions through the creation of sustainable businesses.